2019
DOI: 10.1029/2019jc015222
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Forcings on the Remotely Sensed Phytoplankton Bloom Phenology in the Central Ross Sea Polynya

Abstract: We investigated the interannual variability of the phytoplankton bloom in the central Ross Sea Polynya derived from the annual phenology metrics of the bloom based on ocean color satellite measurements obtained between 2002 and 2017. The phenology metrics determined by the adjusted Gaussian fitting method include the bloom amplitude (BA), bloom initiation timing (BIT), and bloom peak timing (BPT). We found the following results for three phenology metrics. The BA tended to increase since 2002, probably related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 78 publications
2
13
0
Order By: Relevance
“…In 2014, Mangoni et al (2017) reported concentrations up to 202 mg chl a m −2 in the south-central Ross Sea in late January, with a maximum of 4.71 µg L −1 and a UML about 48 m deep and a net dominance of diatoms. The high biomass concentrations reported in this study confirm those reported by Park et al (2019), providing additional information on the timing of productivity and temporal and spatial variability in the central Ross Sea at different scales during summer.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In 2014, Mangoni et al (2017) reported concentrations up to 202 mg chl a m −2 in the south-central Ross Sea in late January, with a maximum of 4.71 µg L −1 and a UML about 48 m deep and a net dominance of diatoms. The high biomass concentrations reported in this study confirm those reported by Park et al (2019), providing additional information on the timing of productivity and temporal and spatial variability in the central Ross Sea at different scales during summer.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, we need to consider that a large part of the biological and physical information on the Ross Sea derive from studies performed in polynya areas or tracks repeated over the year to study the inter-annual variability of the system (DiTullio and Smith et al, 1996, Smith et al, 2006Smith and Gordon, 1997;Saggiomo et al, 1998Saggiomo et al, , 2002Arrigo et al, 2000;DiTullio et al, 2000;Peloquin and Smith, 2007). In recent years, studies on the timing of productivity, distribution of main functional groups, as well as responses of key species to different environmental conditions have generated new questions on the drivers regulating primary production processes in the Ross Sea (e.g., Montes-Hugo and Yuan, 2012;Deppeler and Davidson, 2017;Mangoni et al, 2018Mangoni et al, , 2019Park et al, 2019). Data obtained in this study during the summer 2017, clearly reveal that the Ross Sea is made up by a complex mosaic of sub-systems with physical, chemical, and biological features that change at different temporal and spatial scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During austral spring and summer as the Ross Sea polynya expands due to increasing solar insolation and warming, extensive algal blooms occur that are dominated by the haptophyte Phaeocystis antarctica followed by increased phytoplankton growth of diatoms, mainly the Fragilariopsis species (Asper and Smith, 1999;Arrigo et al, 1999;Smith et al, 2014). Many insights into these bloom dynamics, which are often spatially and temporally distinct, have been obtained from numerous field (DiTullio and Smith, 1996;Smith et al, 1996;DiTullio et al, 2000;Sweeney et al, 2000) and satellite ocean color remote sensing studies (Arrigo et al, 1998a(Arrigo et al, , 1999(Arrigo et al, , 2000Arrigo and Van Dijken, 2003;Park et al, 2019). These studies reported on two regions within the Ross Sea that exhibit physical and biogeochemical differences: (i) the weakly stratified and deeply mixed central Ross Sea polynya surface waters generally dominated by Phaeocystis antarctica, and (ii) the southwest (SW) marginal ice zone with intense surface stratification and shallow mixed layer depths dominated by diatoms.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the OC sensors have been widely used to study various phenomena, such as harmful algal blooms [4], maritime disasters [5][6][7], coral reefs [8] and sediment plumes [9]. In particular, because the chlorophyll-a concentration (CHL, mg m −3 ) in a euphotic zone, which is a representative product derived from the OC measurements, is strongly related to phytoplankton abundance, CHL has a vital role in elucidating the pattern of the phytoplankton growth [10], primary production [11] and global carbon cycle through remotely measured carbon dioxide pressure [12,13] over the global oceans.…”
Section: Introductionmentioning
confidence: 99%